Comparative Pharmacokinetic Profile of 3 Batches of Ovine Low-Molecular-Weight Heparin and 1 Batch of Branded Enoxaparin - Jeske, Walter (Clin Appl Thromb Hemost, 2018)
Although pharmaceutical grade heparin is obtained almost exclusively from porcine intestinal mucosa, there is interest in diversifying heparin sourcing to address potential supply shortages and economically motivated adulteration. Since ovine-derived heparin is structurally similar to porcine heparin, it is expected that ovine-derived low-molecular-weight heparin (LMWH) will be comparable to porcine-derived LMWH. This study compared the pharmacokinetic (PK) behavior of 3 batches of ovine LMWH with that of enoxaparin in nonhuman primates. Blood samples were collected prior to and at 2, 4, and 6 hours post-administration of a 1 mg/kg subcutaneous dose of LMWH. Circulating drug concentrations determined using anti-Xa and anti-thrombin assays were used to calculate values for PK parameters. Tissue factor pathway inhibitor (TFPI) levels were measured by enzyme-linked immunosorbent assay. The ovine LMWHs tested met pharmacopoeial potency and molecular weight distribution requirements for enoxaparin. In the post-administration samples, comparable levels of branded enoxaparin and ovine enoxaparin were observed using anti-Xa and anti-thrombin assays, with the concentration versus time curves being nearly superimposable. Consistent with this similarity, no significant differences were observed between PK parameters calculated for branded enoxaparin and ovine LMWH. The TFPI levels returned to baseline levels by 6 hours in ovine LMWH-treated animals but remained slightly elevated in animals treated with branded enoxaparin. It is concluded that the pharmacokinetics of ovine enoxaparin were not only comparable between different batches but also similar to the branded product. Thus, LMWH prepared from ovine mucosal heparin is comparable to its porcine-derived counterpart.